Effectiveness of the Supplementary Food Program for Pregnant Women with KEK - Lenny Erfianty Sumarno; Endah Mulyani; Amalia Rahma; Dwi Novri Supriatiningrum; Eka Sri Rahayu Ariestiningsih (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pregnant women with CED risk can cause decreased muscle capacity that supports the labor process. This can cause prolonged labor and bleeding that is dangerous for the mother. This study aims to make the program of providing additional food based on local food ingredients for pregnant women with chronic energy deficiency at the Glagah Health Center, Lamongan Regency a success. The design of this study was an experiment with a pretest and posttest design. The location of the study was in the Glagah Health Center, Lamongan. Based on PMT monitoring report data, the study population was all pregnant women with CED based on body weight and LILA indicators used in assessing nutritional status. The sample of this study was all pregnant women in the Glagah area, and used a purposive sampling technique. Statistical tests were carried out using the Paired Sample T-test with a significance value of <0.05. The study showed a significant increase after 4 months of PMT administration and monitoring was carried out which showed a difference in BB and LILA before and after PMT administration with a p value = 0.000. There is effectiveness in providing additional food based on local food ingredients to pregnant women with chronic energy deficiency in the Glagah Lamongan Health Center work area.